2013
DOI: 10.2478/s11658-013-0081-4
|View full text |Cite|
|
Sign up to set email alerts
|

GABA exists as a negative regulator of cell proliferation in spermaogonial stem cells

Abstract: γ-amino butyric acid (GABA) is the main inhibitory neurotransmitter in the mammalian central nervous system. GABA is also found in many peripheral tissues, where it has important functions during development. Here, we identified the existence of the GABA system in spermatogonial stem cells (SSCs) and found that GABA negatively regulates SSC proliferation. First, we demonstrated that GABA and its synthesizing enzymes were abundant in the testes 6 days postpartum (dpp), suggesting that GABA signaling regulates S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…However, when HS significantly reduced the expression of GABA receptor mRNA, the GABA receptor functioned as a negative regulator of HS response, leading to a weakened inhibition. Previous studies have shown that treatment of spermatogonial stem cells with GABA increases the expression of GABA receptor, but inhibits cell proliferation, while treating oocytes with GABA increases the expression of GABA receptor, but reduces estrogen production (Biggs et al, 2013;Du et al, 2013). The animal's body can regulate sexual development and maturation by secreting hormones of the HPG axis, which is the center controlling the development and function of reproductive system in animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, when HS significantly reduced the expression of GABA receptor mRNA, the GABA receptor functioned as a negative regulator of HS response, leading to a weakened inhibition. Previous studies have shown that treatment of spermatogonial stem cells with GABA increases the expression of GABA receptor, but inhibits cell proliferation, while treating oocytes with GABA increases the expression of GABA receptor, but reduces estrogen production (Biggs et al, 2013;Du et al, 2013). The animal's body can regulate sexual development and maturation by secreting hormones of the HPG axis, which is the center controlling the development and function of reproductive system in animals.…”
Section: Discussionmentioning
confidence: 99%
“…, 2013 ), embryonic stem cells ( Ng et al. , 2010 ; Du et al. , 2013 ), myoblasts (in which hyperpolarization driven by the Kir2.1 channel plays a key role; Hinard et al.…”
Section: New Control Knobs: Resting Potential Determines Single-cell mentioning
confidence: 99%
“…A particularly thorough combination of biochemistry, transgenic mouse technology, and electric field perturbation dissected the mechanisms of electrotaxis showing that mammalian wound healing requires cells to sense endogenous fields (generated by trans‐epithelial potential) by a PTEN ‐ and PI(3)K‐γ‐dependent pathway. Cell differentiation is also controlled by changes in V mem , as has been shown in human mesenchymal stem cells, embryonic stem cells, myoblasts (in which hyperpolarization driven by the Kir2.1 channel plays a crucial role), the specification of neurotransmitter types, and the control of precursor differentiation in the developing nervous system and heart. Tissue engineers have also begun to take advantage of this pathway using applied electric field stimulation .…”
Section: Bioelectrical Determinants Of Individual Cell Behaviormentioning
confidence: 90%